A copper inner electrode temperature-stable ceramic dielectric material and preparation method thereof
By using a specific combination of main matrix materials, modification additives and sintering additives, ceramic dielectric materials are formed, and the oxidation failure problem of ceramic dielectric materials when co-fired with copper inner electrodes at low temperatures is solved, and low-temperature sintering of ceramic dielectric materials is achieved And excellent antioxidant properties, suitable for chip multi-layer ceramic capacitors.
Patent Information
- Application Number
- CN202210918590.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-01
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-08-01
AI Technical Summary
Existing ceramic dielectric materials are prone to oxidation failure when co-fired with copper inner electrodes at low temperatures, and the addition of sintering aids affects the dielectric performance, making it difficult to meet the requirements of miniaturization, high reliability, low cost and temperature stability.
Using the main matrix material (Ba1-x-zCaxSrz) (Ti1-yZry)O3, modification additives such as Mn2O3, Mn2Fe2O6, Mn2Al2O6 and sintering additives CaBaSiB4O10, the sintering additives are formed by ball milling and drying, and the low-temperature sintering and anti-reduction properties are formed. Ceramic dielectric material.
It realizes the low-temperature sintering, oxidation resistance and excellent dielectric properties of ceramic dielectric materials. It is suitable for chip-type multi-layer ceramic capacitors, with good temperature stability and durability.
Smart Images

Figure BDA0003776677330000041 
Figure BDA0003776677330000052 
Figure BDA0003776677330000053
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ceramic dielectric materials, specifically to the field of C04B35 / 495, and more specifically to a copper inner electrode temperature-stable ceramic dielectric material and a preparation method thereof. Background Art
[0002] In recent years, electronic products have tended to be small / miniaturized, highly reliable and low-cost. Therefore, the demand for multilayer ceramic capacitors (MLCC) has increased year by year, and higher requirements have been placed on their performance. From the perspective of social and economic benefits and ecological environmental protection, the use of base metal copper (Cu, melting point 1083°C) with a low melting point as the internal electrode of MLCC can effectively reduce production costs; and copper has a low electromigration rate, so it has good electrochemical stability. However, the conditions for base metalization of MLCC internal electrode materials are relatively harsh, requiring the material to be co-fired with copper at a temperature lower than the melting point of the copper electrode; at the same time, in order to prevent the copper electrode from oxidative failure, the material needs to have anti-reduction properties to ensure that it still maintains excellent electrical properties after sintering in a reducing atmosphere.
[0003] Zirconates and titanates of alkaline earth metals such as CaZrO3, SrZrO3, CaTiO3 and BaZrO3 and their solid solutions have good temperature stability and dielectric properties. At present, the method of adding glass frit or sintering aids is usually adopted, such as compounds such as borates and SiO2, and the method of liquid phase sintering is used to achieve the purpose of reducing the sintering temperature of ceramic materials. Its mechanism of action is that low melting point compounds are sintered at a certain temperature and melted into a liquid phase, so that the solid phase is easy to migrate in the liquid phase, and the particles are rearranged, so the sintering temperature can be reduced. However, the addition of glass phase or sintering aids can reduce the content of the main matrix accordingly, causing the dielectric properties of the resulting ceramic materials to be affected to varying degrees. Therefore, the selection and addition of sintering aids need to be suitable and appropriate.
[0004] Compared with the Ni electrode, which is also a base metal inner electrode, the copper electrode is more easily oxidized and needs to be sintered under the condition of reducing atmosphere. In addition, the ceramic dielectric material is easily reduced due to oxygen loss when sintered under high temperature in reducing atmosphere. The oxygen vacancies and variable valence elements generated in this process, and the ionized oxygen vacancies form a large number of electrons, produce high conductivity, and lead to the semiconductorization of the dielectric material, which affects the performance of MLCC. Therefore, the ceramic dielectric material needs to have strong anti-reduction performance before it can be co-fired with the copper inner electrode. The anti-reduction performance of the material can be improved by adding some ions to the ceramic dielectric material. For example, in the CaZrO3 system, Mn 2+ The introduction of ions will be completely integrated into its lattice. As long as the grains are large enough, Mn can be reoxidized. 2+This is because the large-grain ceramics limit the diffusion of oxygen and suppress the concentration of free electrons, thereby effectively improving the reduction resistance of the dielectric material.
[0005] Therefore, it is necessary to provide a dielectric material that meets the requirements of miniaturization, high reliability and low cost, while taking into account low loss, high durability and temperature stability, and at the same time meeting the requirements of sintering at low temperature, excellent anti-reduction performance and good matching with copper internal electrodes. Summary of the invention
[0006] In view of some problems existing in the prior art, the first aspect of the present invention provides a copper inner electrode temperature-stable ceramic dielectric material, which comprises a portion of a main matrix material (Ba 1-x-z Ca x Sr z )(Ti 1-y Zr y )O3, b parts of modifying additives, and c parts of sintering aids, among which 0.1≤x≤0.25, 0.8≤y≤0.95, 0.6≤z≤0.75, 85≤a≤98, 0≤b≤0.8, and 3≤c≤10.
[0007] Preferably, a=95, b=0.75, c=4.35.
[0008] In one embodiment, the raw materials for preparing the main matrix material include one or more of CaCO3, SrCO3, BaCO3, TiO2, and ZrO2.
[0009] Preferably, the preparation method of the main matrix material comprises: as required, ball-milling one or more of CaCO3, SrCO3, BaCO3, TiO2, and ZrO2 in proportion, followed by drying and pre-sintering.
[0010] In a preferred embodiment, the preparation method of the main matrix material includes: as needed, ball-milling one or more of CaCO3, SrCO3, BaCO3, TiO2, and ZrO2 in proportion, then drying, and pre-sintering at 1100°C for 2 hours.
[0011] In one embodiment, the main matrix material is (Ba 0.15 Ca 0.15 Sr 0.7 )(Ti 0.05 Zr 0.95 )O3 or (Ba 0.15 Ca 0.10 Sr 0.75 )(Ti 0.15 Zr 0.85 )O3.
[0012] In one embodiment, the modifying additive is selected from one or more of Mn2O3, Mn2Fe2O6, Mn2Al2O6, and Mn2AlFeO6.
[0013] Preferably, the raw materials for preparing the modified additive are selected from one or more of Mn2O3, Fe2O3, and Al2O3.
[0014] Preferably, the preparation method of the modified additive comprises: as required, ball-milling and mixing one or more of Mn2O3, Fe2O3 and Al2O3 in accordance with a formula ratio, drying, and calcining to obtain the modified additive.
[0015] In a preferred embodiment, the preparation method of the modified additive comprises: as required, ball-milling and mixing one or more of Mn2O3, Fe2O3, and Al2O3 according to a formula ratio, drying, and calcining at 1100°C for 2h to obtain the modified additive.
[0016] In one embodiment, the sintering aid is CaBaSiB4O 10 .
[0017] Preferably, the raw materials for preparing the sintering aid are Ca(BO2)2·2H2O, BaB2O4, and SiO2.
[0018] Preferably, the preparation method of the sintering aid comprises: mixing Ca(BO2)2·2H2O, BaB2O4 and SiO2 uniformly by ball milling at a molar ratio of 1:1:1, drying and pre-sintering at 1050°C for 3 hours to obtain the sintering aid.
[0019] The applicant unexpectedly discovered in the experiment that when the sintering aid is CaBaSiB4O 10 , so that when the addition amount of the sintering aid is 3-10 parts by weight, low-temperature sintering and high durability can be achieved. The possible reason is that the sintering aid makes it easier for the specific main matrix material and other raw materials in this application to form a molten liquid phase, and the particles can migrate and rearrange well.
[0020] In addition, the applicant unexpectedly discovered in the experiment that the modifying additive in the present application is selected from one or more of Mn2O3, Mn2Fe2O6, Mn2Al2O6, Mn2AlFeO6, especially the modifying additive contains Fe 3+ , can be combined with CaBaSiB4O 10The combined effect can improve the density of the ceramic body and reduce the sintering temperature. The sintering temperature range can be reduced to 1000-1060°C, and the dielectric loss is reduced. When the ceramic material is used to prepare MLCC, it has good matching with the copper inner electrode, and exhibits excellent anti-reduction performance and excellent dielectric properties. The applicant analyzed that the reason is that the specific modified additives and sintering aids form a liquid phase and react with the added Al 3+ Reaction: Aluminum ions with smaller radius have higher mobility in cationic subcrystals and can easily enter into the matrix solid solution.
[0021] The second aspect of the present invention provides a method for preparing the copper inner electrode temperature-stable ceramic dielectric material, comprising the following steps:
[0022] (1) Weigh the corresponding main matrix material, modifying additive and sintering aid as required, add deionized water and zirconium balls, ball mill and dry to obtain ceramic powder;
[0023] (2) the obtained porcelain powder is sieved and granulated by adding paraffin wax;
[0024] (3) Pressing the granulated porcelain powder into green discs;
[0025] (4) placing the pressed green disc in a sintering furnace to sinter into porcelain;
[0026] (5) After sintering, the disc is infiltrated with copper to obtain a copper electrode.
[0027] In one embodiment, step (1) includes: weighing the corresponding main matrix material, modifying additive and sintering aid as required, adding deionized water and zirconium balls in a weight ratio of deionized water: material = (1-3): 1, 2.0 mm zirconium oxide ball: material = (3-8): 1, ball milling and mixing, and after ball milling to reach the required particle size, placing in an oven to dry to obtain porcelain powder.
[0028] The materials in step (1) refer to the main matrix material, modifying additives and sintering aids.
[0029] Preferably, the mass ratio of the amount of added water to the total amount of the main matrix material, the modifying additive and the sintering aid is 2:1; the mass ratio of the amount of zirconium balls to the total amount of the main matrix material, the modifying additive and the sintering aid is 5:1.
[0030] In one embodiment, the step (2) comprises: after the obtained porcelain powder is passed through a 50-100 mesh sieve, preferably an 80 mesh sieve, 8-12% by mass of paraffin is added for granulation.
[0031] In one embodiment, the step (3) comprises: pressing the granulated porcelain powder into a green disc with a diameter of 10-15 mm and a thickness of 1.2-1.5 mm at a pressure of 5-10 MPa.
[0032] In one embodiment, step (4) comprises: placing the pressed green disc in a sintering furnace, heating it to 1000-1060° C. at a rate of 10° C. / min in a H 2 atmosphere, keeping the temperature for 1-5 hours, and sintering it into porcelain.
[0033] In addition, under the joint action of the specific main matrix material, modifying additives and sintering aids in this application, the obtained porcelain powder is granulated after passing through a 50-100 mesh sieve, and the green embryo obtained under a specific pressure is simultaneously subjected to 1000-1060°C and kept warm for 1-5 hours. At this time, the electrode obtained has good mechanical strength. The possible reason is that oxygen can escape in time during the sintering process. At an appropriate rate of temperature increase, as the particle size decreases, the material forms a certain dense structure without defects.
[0034] The third aspect of the present invention provides an application of the copper inner electrode temperature-stable ceramic dielectric material in a chip-type multilayer ceramic capacitor.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The temperature-stable ceramic dielectric material for copper inner electrodes of the present application meets the C0G characteristics, has good matching with copper electrodes, excellent anti-reduction performance, and can meet the requirements of low-temperature sintering. The ceramic dielectric capacitor prepared by the ceramic material has excellent properties such as low dielectric loss, good temperature stability and durability. In addition, the ceramic material in the present application has good matching with the copper inner electrode when used to prepare MLCC, and exhibits excellent anti-reduction performance and excellent dielectric properties. DETAILED DESCRIPTION
[0037] The present invention is described below by specific implementation methods, but is not limited to the specific embodiments given below.
[0038] Examples 1-5
[0039] A copper inner electrode temperature-stable ceramic dielectric material, the raw material for preparation is specifically a main matrix material (Ba 1-x- z Ca x Sr z )(Ti 1-y Zr y )O3, modified additives, sintering aids CaBaSiB4O 10 .
[0040] The modifying additives of each embodiment are shown in Table 1 below, in units of moles.
[0041] Table 1
[0042]
[0043]
[0044] The main matrix material of each embodiment is shown in Table 2 below, in moles.
[0045] Table 2
[0046]
[0047] The formula of the sintering aid is shown in Table 3 below, in moles.
[0048] Table 3
[0049]
[0050] The raw material ratio of each example is shown in Table 4 below, in units of weight percentage.
[0051] Table 4
[0052] Example BCSTZ1 BCSTZ2 <![CDATA[Mn2O3]]> <![CDATA[Mn2Fe2O6]]> <![CDATA[Mn2Al2O6]]> <![CDATA[Mn2AlFeO6]]> <![CDATA[CaBaSiB4O 10 ]]> 1 95 / 0.75 / / / 4.35 2 95 / / 0.75 / / 4.35 3 95 / / / 0.75 / 4.35 4 95 / / / / 0.75 4.35 5 / 95 / / / 0.75 4.35
[0053] The preparation method is as follows:
[0054] (1) CaCO3, SrCO3, BaCO3, TiO2 and ZrO2 were mixed according to the chemical formula (Ba 1-x-z Ca x Sr z )(Ti 1-y Zr y )O3 in corresponding molar ratios, mixed and ball-milled, dried and pre-sintered at 1100° C. for 2 hours to obtain a main matrix material powder;
[0055] (2) mixing one or more of Mn2O3, Fe2O3 and Al2O3 uniformly by ball milling according to corresponding formula ratios, drying and pre-sintering at 1100°C for 2 hours to obtain a modified additive powder;
[0056] (3) Ca(BO2)2·2H2O, SiO2, and BaB2O4 were mixed according to the chemical formula CaBaSiB4O 10 The formula ratio is weighed, ball-milled and mixed evenly, and then pre-sintered at 1050° C. for 3 hours after drying to obtain a sintering aid powder.
[0057] (4) Weigh the corresponding main matrix material powder, modified additive and sintering aid powder in a formula ratio of 95:0.75:4.35 by weight, add deionized water and zirconium balls in a weight ratio of deionized water: material = 2:1, 2.0 mm zirconium oxide ball: material = 5:1, ball mill and mix, and after ball milling to the required particle size, place in an oven for drying to obtain a ceramic powder;
[0058] (5) The obtained porcelain powder is passed through an 80-mesh sieve and granulated by adding 10% by mass of paraffin wax;
[0059] (6) Pressing the granulated porcelain powder into a green disc with a diameter of 15 mm and a thickness of 1.5 mm under a pressure of 8 MPa;
[0060] (7) placing the pressed green disc in a sintering furnace, heating it to 1050°C at a rate of 10°C / min in a H2 atmosphere, keeping the temperature for 3 hours, and sintering it into porcelain;
[0061] (8) After sintering, the disc is infiltrated with copper electrodes and its dielectric properties are tested.
[0062] Performance Evaluation
[0063] 1. Dielectric constant: Use KEYSIGHT E4981A dielectric constant tester with a test frequency of 1MHz to calculate the dielectric constant through the capacitance of the sample. The calculation formula is as follows:
[0064]
[0065] Where: ε is the dielectric constant of the sample;
[0066] C is the capacitance of the sample, pF;
[0067] h is the thickness of the sample, cm;
[0068] D is the diameter of the sample, cm.
[0069] 2. Dielectric loss: The dielectric loss of the sample was tested using a KEYSIGHT E4981A permittivity tester with a test frequency of 1 MHz.
[0070] 3. Insulation resistance: Use HEWLETT PACKARD 4339B high resistance meter to test. The test value is the volume resistance of the sample. The insulation resistance is calculated by the following formula:
[0071]
[0072] Where: v is the insulation resistance of the sample, in Ω·cm;
[0073] R is the volume resistance of the sample, in Ω;
[0074] D is the diameter of the sample, in cm;
[0075] d is the thickness of the sample in cm.
[0076] 4. Temperature coefficient: Use KEYSIGHT E4981A capacitance tester, test frequency is 1MHz, test temperature range is -55℃~125℃, and capacitance temperature coefficient is calculated according to the following formula:
[0077]
[0078] Where: α c is the capacitance temperature coefficient of the sample, ppm / K;
[0079] is the capacitance of the sample at different temperatures, pF;
[0080] is the capacitance of the sample at room temperature, pF;
[0081] Δt is the difference between the test temperature and room temperature, °C.
[0082] The test results are shown in Table 5.
[0083] Table 5
[0084]
Claims
1. A copper inner electrode temperature-stable ceramic dielectric material, characterized in that: By weight, the raw materials include a part of main matrix material (Ba 1-x-z Ca x Sr z )(Ti 1-y Zr y )O3, b parts of modifying additives, c parts of sintering aids, wherein x=0.10, y=0.85, z=0.75, a=95, b=0.75, 3≤c≤10; the modifying additive is Mn2AlFeO6, the sintering aid is CaBaSiB4O 10 .
2. The copper inner electrode temperature-stable ceramic dielectric material according to claim 1, characterized in that: The main matrix material (Ba 1-x-z Ca x Sr z )(Ti 1-y Zr y )The raw materials for preparing O3 include one or more of CaCO3, SrCO3, BaCO3, TiO2, and ZrO2.
3. A method for preparing the copper inner electrode temperature-stable ceramic dielectric material according to any one of claims 1-2, characterized in that: The following steps are included: (1) Weigh the corresponding main matrix material, modification additive and sintering aid as required, add deionized water and zirconium balls, ball mill and dry to obtain ceramic powder; (2) The obtained porcelain powder is sieved and granulated by adding paraffin wax; (3) Pressing the granulated porcelain powder into green discs; (4) placing the pressed green disc in a sintering furnace to sinter into porcelain; (5) After sintering, the disc is infiltrated with copper to obtain the electrode.
4. The method for preparing the copper inner electrode temperature-stable ceramic dielectric material according to claim 3, characterized in that: The mass ratio of the amount of water added in the step (1) to the total amount of the main matrix material, the modifying additive and the sintering aid is (1-3):1; the mass ratio of the amount of zirconium balls to the total amount of the main matrix material, the modifying additive and the sintering aid is (3-8):
1.
5. The method for preparing the copper inner electrode temperature-stable ceramic dielectric material according to claim 4, characterized in that: In step (2), the ceramic powder is passed through a 50-100 mesh sieve.
6. The method for preparing the copper inner electrode temperature-stable ceramic dielectric material according to claim 4 or 5, characterized in that: The step (3) comprises: pressing the granulated porcelain powder into a round green sheet with a diameter of 10-15 mm and a thickness of 1.2-1.5 mm under a pressure of 5-10 MPa.
7. The method for preparing the copper inner electrode temperature-stable ceramic dielectric material according to claim 6, characterized in that: The sintering conditions in step (4) are: hydrogen atmosphere, heating to 1000-1060°C at a rate of 10°C / min, and keeping warm for 1-5h.
8. Use of the copper inner electrode temperature-stable ceramic dielectric material according to any one of claims 1 to 2 in a chip-type multilayer ceramic capacitor.
Citation Information
Patent Citations
Anti-reduction low temperature-sintered high-frequency thermal stability dielectric ceramic and preparation method thereof
CN104003716A